The effects of job satisfaction on lecturer performance : case study in faculty x Universitas Indonesia - Sancoko Sancoko; Rahmat Yuliawan; Badra Al Aufa; Heri Yuliyanto (Jurnal Pendidikan Teknologi dan Kejuruan, 2023)
Job satisfaction needs to be considered by the organization because based on the theory, job satisfaction affects employee performance. This study aims to evaluate the influence of job satisfaction on the lecturer performance in the faculty X Universitas Indonesia. This study uses quantitative approach to answer the five hypothesis. The population in this study were all permanent lecturers at faculty X, totally 66 people. The data is obtained through structured questionnaire distributed to permanent lecturer. The instrument was tested using validity and reliability tests; afterwards data were analyzed use correlation and multiple regression. The regression results prove that job satisfaction with salary has a significant effect on lecturer performance. For indicators job satisfaction with promotion, co-worker and faculty leader have not significant influence.